Problematika Hubungan Sosial Kaum Salafi di Sumatera Barat - Cahya, Nilam; Efendi; Rais, Zaim (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
This article aims to review various problems of social relations of Salafis in West Sumatra based on literature review from various sources in recent years. The research method used is a qualitative method of the type of literature study. The results of the literature review that have been conducted show that Salafis have good social relations in the family, neighbors, and friendship with Salafis and non-Salafis. However, Salafis also have an exclusive nature with the surrounding community in terms of worship or muamalah which according to them is contrary or incompatible with Al-Quir'an, Hadith, and the actions exemplified by as-salaf ash-salih which are the main sources of Salafi Islamic teachings. In addition, there is also a social gap from the case of Ustadz Hafzan El Hadi which has occurred on Eid al-Fithri in 1444 H / 2023 AD where the case is about the difference in the determination of Eid al-Fithri between the Government and Muhammadiyah. He compared Muhammadiyah to Shi'a in posts posted on social media. He eventually apologized to Muhammadiyah. However, the legal process continues.These are various problems in social relations between Salafis and non-Salafi communities in the West Sumatra area.